2015
DOI: 10.1371/journal.pone.0127148
|View full text |Cite
|
Sign up to set email alerts
|

Can We Improve Structured Sequence Processing? Exploring the Direct and Indirect Effects of Computerized Training Using a Mediational Model

Abstract: Recent research suggests that language acquisition may rely on domain-general learning abilities, such as structured sequence processing, which is the ability to extract, encode, and represent structured patterns in a temporal sequence. If structured sequence processing supports language, then it may be possible to improve language function by enhancing this foundational learning ability. The goal of the present study was to use a novel computerized training task as a means to better understand the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Future research could fruitfully attempt to disentangle the causal nature of this relationship. This may be achieved for instance through training studies that attempt to increase SL ability and then test if language performance improves via cognitive transfer (Conway, Gremp, Walk, Bauernschmidt, & Pisoni, 2012; Smith, Conway, Bauernschmidt, & Pisoni, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Future research could fruitfully attempt to disentangle the causal nature of this relationship. This may be achieved for instance through training studies that attempt to increase SL ability and then test if language performance improves via cognitive transfer (Conway, Gremp, Walk, Bauernschmidt, & Pisoni, 2012; Smith, Conway, Bauernschmidt, & Pisoni, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Nouchi et al (2013) suggest that adaptive cognitive training techniques in particular reveal far transfer effects. Furthermore, new research on brain training programs has been shown to manifest both near transfer and far transfer of training-specified tasks as well as other non-trained cognitive functions (Smith et al, 2015). Encouraging outcomes following cognitive training include significant post-training improvement in working memory (Dahlin, 2013), processing speed (Gibson et al, 2015), and general intelligence (Jausovec and Jausovec, 2012;Carpenter et al, 2016).…”
Section: Cognitive Training Effects On Cognitionmentioning
confidence: 99%
“…If untreated, issues related to poor language comprehension and social competency can extend beyond adolescence and into adulthood, causing further problems related to employment and education. With that in mind, research has shown that training programs aimed at improving temporal and sequential processing capacities can bolster the recognition of speech and non-speech temporal sequences in children with language impairments 89 as well as language processing in non-ASD adults 90 . Therefore, incorporating activities into therapies and interventions that encourage pattern and sequence learning may help non-ASD and ASD individuals learn these patterns and probabilities more readily.…”
Section: Discussionmentioning
confidence: 99%